2006
DOI: 10.1159/000095181
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin Modulation of TGF-ß1-Induced Collagen Synthesis is Dependent on ERK1/2 MAPK Activation

Abstract: Background/Aims: Transforming growth factor-β1 (TGF-β1) plays a pivotal role in the extracellular matrix accumulation observed in fibrotic diseases. Endoglin is an important component of the TGF-β receptor complex highly expressed in tissues undergoing fibrotic processes. Endoglin expression regulates the effect of TGF-β on extracellular matrix synthesis. The purpose of our study has been to understand the molecular mechanism by which endoglin exerts its effects on fibrosis and the possible role of MAP kinases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 30 publications
0
33
0
1
Order By: Relevance
“…It should be also noted that endoglin is involved in cell adhesion, cell migration (Bernabeu et al, 2007), and the synthesis of matrix proteins such as collagen (Rodríguez-Barbero et al, 2006). Adhesion molecules and matrix proteins play an important role in osteoblast functions and bone remodeling (Damsky, 1999;Bennett et al, 2001); thus investigation from this point of view should be also necessary to elucidate mechanisms underlying our findings.…”
Section: Discussionmentioning
confidence: 80%
“…It should be also noted that endoglin is involved in cell adhesion, cell migration (Bernabeu et al, 2007), and the synthesis of matrix proteins such as collagen (Rodríguez-Barbero et al, 2006). Adhesion molecules and matrix proteins play an important role in osteoblast functions and bone remodeling (Damsky, 1999;Bennett et al, 2001); thus investigation from this point of view should be also necessary to elucidate mechanisms underlying our findings.…”
Section: Discussionmentioning
confidence: 80%
“…Endoglin is a potent mediator of profibrotic effects of angiotensin II on cardiac fibroblasts and can modulate the effect of TGF-b1 on extracellular matrix synthesis. 18,19 In this study, we have demonstrated that pretreatment with valsartan, an angiotensin-receptor antagonist, can reduce myocardial fibrosis through reducing endoglin expression after MI. The effect of inhibition of miR-208a induced by MI occurred earlier with valsartan than with atorvastatin because valsartan, but not atorvastatin, had an inhibitory effect on miR208a expression after 3 days of AMI.…”
Section: Discussionmentioning
confidence: 82%
“…17 Endoglin is a potent mediator of profibrotic effects of angiotensin II on cardiac fibroblasts and can modulate the effect of TGF-b1 on extracellular matrix synthesis. 18,19 These data indicate that endoglin may play an important role in fibrogenesis in cardiac remodelling. We have previously demonstrated that miR-208a can increase endoglin expression in cardiac myoblasts and in volume-overloading heart failure to modulate myocardial fibrosis.…”
mentioning
confidence: 85%
“…Activation of the renin-angiotensinaldosterone system (RAAS) stimulates transforming growth factor-β (TGF-β) expression in the kidney through various mechanisms and upregulates receptors for TGF-β. TGF-β is one of the key factors stimulating synthesis of collagen and other extracellular matrix components [8,9]. Recent findings show that TGF-β induces a rapid but transient accumulation of Egr-1 transcripts and protein in human skin fibroblasts [10].…”
Section: Introductionmentioning
confidence: 99%